Respuesta :

Answer:

m = 1/2 or m = -3

Step-by-step explanation:

m(2m + 5) = 3

Distribute the m on the left side.

2m² + 5m = 3

Subtract 3 from both sides.

2m² + 5m - 3 = 0

Try factoring the trinomial.

(2m - 1)(m + 3) = 0

2m - 1 = 0 or m + 3 = 0

2m = 1 or m = -3

m = 1/2 or m = -3

Answer:

[tex]2m ^{2} + 5m = 3[/tex]

Step-by-step explanation:

[tex]m(2m \ + 5) = 3 \\ you \: multiply \: m \: with \: what \: is \: in \: the \: bracket \: which \: is \: equal \: to \: \\ 2m ^{2} + 5m = 3[/tex]